Women’s Sport Communities: Communication, Motivations, and Self-Contentment Beyond the Finish Line of RunWMe - Munawan, Nur Salsabil; Destyarini, Erika; Firdhausyah, Feima Sarah (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
Sport is an easy and accessible activity to individuals of all backgrounds which has indirectly fostered a sense of friendship and belonging, especially amongst women. Through sports communities, women forge bonds that create a safe space, enabling them to move freely in public spaces. This paper is aiming to understand several intersections between women, sports communities, and marketing strategies, as well as delving into the motives, experiences, and communication strategies of the women in RunWMe community. Through in-depth interviews with five selected participants, the study draws upon the Social Capital Theory which highlights the role of social networks in promoting collaboration and collective action to address shared challenges. The result showed deeper insights into community empowerment and women’s personal experiences in achieving self-contentment through community engagement, and how the right sports communities can strengthen bonds and support among women in the community.